Happy Danes and Deep Incarnation. (2nd September 2013) - Peters, Ted
Abstract: The new Copenhagen School of Deep Incarnation posits that, in Jesus Christ, God has become incarnate and therefore present "in, with, and under" all physical and biological processes. This claim raises the issue of "compatibilism, " according to which divine action and creaturely action are compatible, and "incompatibilism, " according to which divine action must be absent to allow for free creaturely action. Niels Henrik Gregersen, representing the Copenhagen School, affirms both compatibilism at the quantum level of physical activity and incompatibilism at the level of nature's self‐organization. This article points out the incoherence of this position along with the positions proffered by process theologians and kenotic theologians.